Effect of thermal annealing on nanostructure and shape transition in SiC–C nanocomposites - Zhu, Y.; Zhou, Z.; Lu, Chunsheng; Liao, X.; Shen, Y. (American Scientific Publishers, 2012)
Controllable low-temperature (500 °C) deposition of SiC–C (3–10 vol.%C) composite ceramic films on Si(100) was achieved using a pulsed dc-magnetron puttering system in a mixture of CH4/Ar, followed by annealing in 600–1000 °C. At annealing temperatures of 800 °C or above, the formation of equiaxed SiC nanocrystals (NCs) was accompanied by near-elongated nano-C (graphite). These SiC NCs are chemically pure, highly stoichiometric, and have typical sizes of 6–24 nm. After further annealing at 1000 °C, SiC NCs were also in the form of regular grains with an average size of ~55 nm, whereas elongated nano-C grains were transformed to graphite nanorods (NRs) with widths of 5–20 nm and lengths of 30–120 nm. The greatly enhanced mechanical properties of SiC–C nanocomposites are attributed to their improved nanostructure comprising of SiC NCs surrounded by nano-C NR matrices. The formation of graphite NRs is also interpreted by an oxide-assisted growth mechanism.